Governance of Acting Regional Heads and Its Implications for National Resilience - Thaher, Irmanjaya; Isnaini (Jurnal Lemhannas RI, 2025)
Purpose: This research describes how much the selection of acting regional heads by the central government does not run as per the constitutional principles, local democracy and national resilience which are through the Asta Gatra framework but more politically captured by offering a model of governance that is more accountable and participatory. Study Design/Methodology/Approach: Normative legal method with narrative review and comparative analyses of legislation, Constitutional Court decisions, and national and international academic literature to map the correlation between legal legitimacy, institutional design and regional government stability the research applies a normative legal method combined with a narrative review and comparative analyses of legislation, Constitutional Court decisions, and national and international academic literature in order to map the correlation between legal legitimacy, institutional design, and regional government stability. Findings: The findings reveal that the higher-level leadership appointment system has substantial regulatory vacancies, especially in terms of authority restriction, legislative supervision, selection transparency and performance responsibility. These contradictions are affecting the political, governance and social aspects of Asta Gatra so that it can drain the drain the power of regional legitimacy and institutional resilience. Country illustrations, like in Germany, India, and South Africa, show that support for interim leadership is normally subject to legislative endorsement and public scrutiny, with terms of office limited to democratic insurance coverage. Originality/Value: This conceptual contribution is presented to the development of an institutional design for regional leadership transitions that is more democratic and adaptive to national resilience needs. Recommendations focus on regulatory reform, involvement of the Regional People's Representative Council (DPRD), and strengthening public evaluation to ensure the appointment of Acting Regional Heads aligns with substantive democratic principles and strengthens regional autonomy.